Tribute to Dr James Williams - Cooke, Robin (Victoria University of Wellington Law Review, 1999)
A memorial service was held at Victoria University to honour the life and work of Dr JamesWilliams, former Professor of English and New Zealand Law, Principal and then first Vice-Chancellor of the Victoria University of Wellington, who died suddenly at his home in Sydney on Monday, 12 January 1976.Mr Justice Cooke spoke of Dr Williams and his contribution to the law.